Impact of COVID-19 infection on maternal near miss cases in tertiary care centre - Chavan, Niranjan; Mahapatra, Shalini; Venkateswaran, Sneha; Ponkshe, Jui; Nayak, Arun H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has exposed vulnerable populations to a health crisis. Since the beginning of the severe acute respiratory syndrome (SARS-CoV-2) or COVID-19 outbreak, it has been argued whether pregnant women are at increased risk of severe infection.1 The objective of this study was to summarize the effect of COVID-19 on maternal near miss cases. Methods: This single-centre prospective observational study, included all consecutive pregnant women with COVID-19 infection admitted to Lokmanya Tilak Municipal Medical College and General Hospital (Mumbai, India), a tertiary referral hospital, from 1 April 2020, to 20 December 2020. In this study, a total of 46 patients were included in near miss cases, who required ICU admission with severe morbidity. Of these, 8 patients were COVID-19 positive and remaining 38 patients were included in control group (COVID-19 negative). The course of each of their stay in ward was noted and findings were compared in both the groups. Results: During their course in ICU it was found that 6 COVID-19 patients had maternal death representing 75% and 12 non-COVID-19 patients had maternal death representing 31.57%. Conclusions: The mortality rate from the above results concludes that in this study mortality appeared to be higher in COVID-19 infection. Multi-centre retrospective analysis with larger population size is required in order for this to be statistically significant.